Castle Gap and the Pecos Frontier, Revisited. - Dearen, Patrick (TCU Press, 2017)
First published in 1988, Castle Gap and the Pecos Frontier was acclaimed by reviewers as "superb," "significant," and "utterly delightful." In this revised edition, Patrick Dearen draws upon the latest in scholarship to update his study of the Pecos River country of West Texas. It?s a land wild with tales that blend history, geography, and folklore, and from his search emerge six fascinating accounts: -Castle Gap, a break in a mesa twelve miles east of the Pecos River, used by Comanches, emigrants, stage drivers, and cattle drovers; -Horsehead Crossing, the most infamous ford of the Old West; -Juan Cordona Lake, a salt lake where sandstorms and skull-baking sun defied early efforts to mine salt vital to survival; -The "bulto" or ghost who wanders the Fort Stockton night; -Lost Wagon Train, a forty-wagon caravan buried in the sands; -The lost mine of Will Sublett, who found gold and kept its location secret unto death. Although linked by the search for treasure, the stories are as varied as the land itself. They speak eloquently of the Pecos country, its heritage, and its people.